2005
DOI: 10.1111/j.1365-2761.2005.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Histidine nutrition and genotype affect cataract development in Atlantic salmon, Salmo salar L.

Abstract: The aim of this study was to investigate effects of dietary levels of histidine (His) and iron (Fe) on cataract development in two strains of Atlantic salmon monitored through parr-smolt transformation. Three experimental diets were fed: (i) a control diet (CD) with 110 mg kg )1 Fe and 11.7 g kg )1 His; (ii) CD supplemented with crystalline His to a level of 18 g kg )1 (HD); and (iii) HD with added iron up to 220 mg kg )1 (HID). A cross-over design, with two feeding periods was used. A 6-week freshwater (FW) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(131 citation statements)
references
References 44 publications
8
123
0
Order By: Relevance
“…The early part of salmon development is spent in freshwater as parr followed by transformation to smolts before entering the sea. Despite the physiological changes associated with parr-smolt transformation, a preadaption for life in seawater, reversible osmotic cataracts, are commonly described immediately after seawater transfer (9, 22), and irreversible cataracts, which also develop soon after transfer, are often seen in seawater fish (7,9,31). There is additional evidence that osmotic stress may cause cataract in farmed salmon since the appearance of cataract was shown to be increased by environmental fluctuations in salinity (4).…”
mentioning
confidence: 99%
“…The early part of salmon development is spent in freshwater as parr followed by transformation to smolts before entering the sea. Despite the physiological changes associated with parr-smolt transformation, a preadaption for life in seawater, reversible osmotic cataracts, are commonly described immediately after seawater transfer (9, 22), and irreversible cataracts, which also develop soon after transfer, are often seen in seawater fish (7,9,31). There is additional evidence that osmotic stress may cause cataract in farmed salmon since the appearance of cataract was shown to be increased by environmental fluctuations in salinity (4).…”
mentioning
confidence: 99%
“…insufficient dietary His supply), the lens may utilise other osmolytes. Breck et al (2005a), for example, showed that the sum of free amino acids in Atlantic salmon lenses was relatively constant, despite variations in the concentration of NAH induced by different diets. The results of the present study suggest, however, that utilisation of NAH might be more efficient in lens osmoregulation than efflux of other amino acids to compensate for low His and NAH concentrations, as the P-lenses showed a greater volume change than did the M-lenses.…”
Section: Discussionmentioning
confidence: 99%
“…The osmolality of the control medium was chosen to equate to the aqueous humour osmolality in vivo, previously measured by (Breck et al, 2005a). Medium osmolality was adjusted by addition of either NaCl or de-ionised Milli-Q water (Millipore, Billerica, USA).…”
Section: Lens Culture and Osmotic Challengementioning
confidence: 99%
See 2 more Smart Citations